Thermal tolerance plasticity under stress: the impact of a marine heatwave and bleaching in the various life stages of Berghia stephanieae - Silva, Ruben X. G.; Calado, Ricardo; Madeira, Diana (Frontiers in Marine Science, 2025)
With the increasing intensity and duration of marine heatwaves (MHW), there has been a corresponding rise in bleaching events. These events cause severe ecological impacts, yet most studies have focused on directly impacted or economically important species, such as corals and fish. However, the impacts of heat-induced bleaching on specialized predators, particularly those that feed on prey susceptible to bleaching, remain largely unknown. This gap of knowledge is especially concerning given that many of these specialized species have complex life cycles, for which stage specific tolerance is poorly characterized, and have narrow geographic ranges, potentially increasing their vulnerability to environmental change. Here, we tackle this issue by studying the impact of a MHW event and bleaching of prey on the thermal plasticity throughout the life cycle of the stenophagous nudibranch, Berghia stephanieae. We tested the Critical Thermal Maxima (CTmax) of embryos, juveniles and adults of Berghia stephanieae. We found that while none of the tested treatments significantly impacted B. stephanieae’s CTmax, juveniles had a significantly lower CTmax than the remaining life stages under optimal conditions. We also found that survival decreases under MHW conditions, particularly in embryos, that failed to survive past four days of exposure. Lastly, heat tolerance plasticity was minimal in this species. These findings highlight this nudibranch’s limited acclimation capacity for acute thermal stress, and that the tolerance of its early life stages will most likely be the most critical for its survival under future extreme climate scenarios.